2021
DOI: 10.1108/jfep-11-2019-0245
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between financial development and effectiveness of monetary policy: new evidence from ASEAN-3 countries

Abstract: Purpose This paper aims to investigate the relationship between financial development (FD) and monetary policy effectiveness (MPE) on output and inflation in ASEAN-3 countries (Singapore, Malaysia and the Philippines). Design/methodology/approach This study uses an open economy structural vector autoregressive model to generate MPE. Then, an autoregressive distributed lagged (ARDL) model is used to analyze the effect of FD on MPE across countries. Findings The findings revealed that FD plays a different ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(59 reference statements)
3
2
0
1
Order By: Relevance
“…This outcome implies that a more efficient monetary policy with a less developed financial institution would be more stable in the market system in developing countries. This result was in line with Samba and Mbassi (2016) and Karim et al (2021), who stated that the effect of MPE and FMD on financial stability was a substitute. However, these findings contradicted Ma and Lin (2016), who found a complementary effect of MPE and FMD on financial stability.…”
Section: Results Of Pooled Mean Group Estimationsupporting
confidence: 88%
See 1 more Smart Citation
“…This outcome implies that a more efficient monetary policy with a less developed financial institution would be more stable in the market system in developing countries. This result was in line with Samba and Mbassi (2016) and Karim et al (2021), who stated that the effect of MPE and FMD on financial stability was a substitute. However, these findings contradicted Ma and Lin (2016), who found a complementary effect of MPE and FMD on financial stability.…”
Section: Results Of Pooled Mean Group Estimationsupporting
confidence: 88%
“…This result implied that the influence of MPE on the credit gap is more prominent in the high-middle income group. This finding was in line with Alpanda and Zubairy (2019) and Karim et al (2021), who found that MPE was the main factor in reducing the credit gap in high-income countries. Furthermore, MPE has increased the overall stability of the financial markets of developing countries, with the effect being greater in high-middle-income nations.…”
Section: Split Samplesupporting
confidence: 89%
“…Finally, the coefficient of the money supply is positive and significant at a 5% level. The result shows that one one-unit growth in money supply, there would be, on average, 2.6-unit increase in FD, holding other factors constant, and the findings align with the studies (Khan, 2005; Abdul Karim et al , 2021). The plausible reason is that the increase in the availability of stock of money and the credit opportunities at the lower interest rates thus leads the FD to broaden its role in lending activities.…”
Section: Empirical Results and Discussionsupporting
confidence: 86%
“…The theoretical and empirical support of the demand-following hypothesis can be found in the earlier studies of Ang and McKibbin (2007), Ratsimalahelo and Barry (2010); and Dar and Nain (2023). However, Nain and Kamaiah (2014), Cherif and Dreger (2016) and Abdul Karim et al (2021) did not find any evidence in favour of EG being a significant determinant of FD in the case of emerging countries. The difference in these cited studies could be attributed to the fact that the finance–growth relationship may be subject to some macroeconomic fundamentals, of which inflation could be a major one.…”
Section: Introductionmentioning
confidence: 75%
“…Saraswati et al (2020) revealed that both in the short and long run, financial inclusion showed significant impact on inflation rate, which worked as a proxy for the effectiveness of monetary policy in Indonesia during 2009–2018. In ASEAN 3 countries, Karim et al (2021) found that a more settled stock market capitalization led to improve MP effectiveness on output in Singapore. Further, the study found that in case of the Philippines, the influence of FD (liquid-liabilities) upon MP effectiveness on output is reliant on the interest rate.…”
Section: Literature Reviewmentioning
confidence: 99%